GENERAL UNDERSTANDING OF HYPERTROPHIC AND POLYPOSIS RHINITIS, INFORMATION ON ITS INCIDENCE, PATHOGENESIS (World Bulletin of Public Health, 2024)
This article presents literature data on the incidence, causes, pathogenesis and pathomorphological types of hypertrophic and polypous rhinitis. Chronic hypertrophic and polypous rhinitis is a process of neoplastic growth of tissues, in which both parenchyma and stromal structures proliferate simultaneously. Exogenous and endogenous factors that cause a vasomotor reaction in the mucous membrane are distinguished as causes. Exogenous influences include cold, factors that provoke reflexes, smoke, sharp and spicy foods, meteomils, and various drugs, which have a vasoconstricting and hypotensive effect. Among the endogenous factors, hormonal dysfunction, endocrine diseases and physical psychoemotional effects gain great importance. Morphologically, simple, allergic and fibromatous types of this disease are distinguished.
Keywords: nose; rhinitis; hypertrophy